Helping young refugees avoid exploitative living arrangements - Anderson, M; Beston, C (Refugee Studies Centre, University of Oxford, 2012)
In an urban environment, the relationship between an unaccompanied young refugee and his or her host family is critical, often making the difference between a life of protection and one of exploitation